A New Model for Predicting Hypothyroidism After Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma - Peng, Liang; Mao, Yan-Ping; Huang, Cheng-Long; Guo, Rui; Ma, Jun; Wen, Wei-Ping; Tang, Ling-Long (Frontiers in Oncology, 2020)
Objectives: To develop a model that can predict the risk of hypothyroidism (HT) after intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC), and to accordingly recommend dose constraints. Materials and methods: NPC patients treated between 2011 and 2015 were retrospectively reviewed. HT was defined by an abnormally high level of thyrotropin. The dosimetry parameters Vx (percentage of thyroid volume receiving more than x Gy of radiation) and Va,b (percentage of thyroid volume receiving > a Gy, while ≤ b Gy radiation) were calculated. The primary endpoint was the development of HT within the first 2 years after IMRT. The least absolute shrinkage and selection operator and multivariate logistic regression were used to identify predictors of HT. Results: A total of 545 patients were included in the analyses, with a median follow-up of 36 months. Of the 545 patients, 138 developed HT within 2 years, and the 2-year incidence of HT was 25.3%. In patients with thyroid volume > 20 cm3, the 2-year incidence of HT was 11.68% (16/137); in patients with thyroid volume ≤ 20 cm3 and V30,60 ≤ 80%, the 2-year HT incidence was 19.9% (33/166); in patients with thyroid volume ≤ 20 cm3 and V30,60 > 80%, the 2-year incidence of HT was 36.8% (89/242). Conclusion: Thyroid volume and V30,60 could be reliable predictors of HT after IMRT for NPC. For patients with thyroid volume ≤ 20 cm3, thyroid V30,60 ≤ 80% might be a useful dose constraint to adopt during IMRT planning.